2014
DOI: 10.2174/1389202915666140616233211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Next Generation Sequencing Techniques in Food Microbiology

Abstract: Understanding the Maxam-Gilbert and Sanger sequencing as the first generation, in recent years there has been an explosion of newly-developed sequencing strategies, which are usually referred to as next generation sequencing (NGS) techniques. NGS techniques have high-throughputs and produce thousands or even millions of sequences at the same time. These sequences allow for the accurate identification of microbial taxa, including uncultivable organisms and those present in small numbers. In specific application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(89 citation statements)
references
References 128 publications
1
87
0
1
Order By: Relevance
“…Similar results were obtained with aromatic spices [27]. Furthermore, the integration of metabolomics technique with other technologies is important to allow the link among microbial metabolites and sensorial attributes [28].…”
Section: Food Qualitysupporting
confidence: 74%
“…Similar results were obtained with aromatic spices [27]. Furthermore, the integration of metabolomics technique with other technologies is important to allow the link among microbial metabolites and sensorial attributes [28].…”
Section: Food Qualitysupporting
confidence: 74%
“…It is characterized by a high-throughput data yield from a single run. HTS or NGS is the catch-all term used to describe a number of modern sequencing techniques including Roche/454 technology, Illumina (Solexa) technology, ABI SOLiD technology, Ion torrent: Proton/PGM sequencing and PacBio SMRT (Mayo et al, 2014). It has provided new platforms to investigate all kinds of microbial communities and to discover some rare and even unknown species.…”
Section: Introductionmentioning
confidence: 99%
“…These sequences help in identifying rarely culturable or unculturable microbes in a sample. HTS also gives an accurate inventory of all microbial operons and genes that are present or are expressed under certain study conditions (Mayo et al, 2014). Compared to DGGE, HTS can provide more detailed information with digitalized results (Ling et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the introduction of newly developed sequencing strategies, commonly referred to as next-generation DNA sequencing techniques, has substantially revolutionised the study of genomics and molecular biology, being also successfully applied in food microbiology (Mayo et al 2014). However, the recent few studies exploiting and comparing high-throughput sequencing and PCR-DGGE surprisingly demonstrated how the latter technique still represents a valid tool for the profiling of complex food microbial communities (Delgado et al 2013;Garofalo et al 2015).…”
Section: Introductionmentioning
confidence: 99%